A miniature tunable quadrature shadow oscillator with orthogonal control - Seangrawee Buakaew; Chariya Wongtaychatham (Institute of Advanced Engineering and Science, 2023)
This article presents a new design of a quadrature shadow oscillator. The oscillator is realized using one input and two outputs of a second-order filter cell together with external amplifiers in a feedback configuration. The oscillation characteristics are controlled via the external gain without disturbing the internal filter cell, following the concept of the shadow oscillator. The proposed circuit configuration is simple with a small component-count. It consists of, two voltage-different transconductance amplifiers (VDTAs) along with a couple of passive elements. The frequency of oscillation (FO) and the condition of oscillation (CO) are controlled orthogonally via the dc bias current and external gain. Moreover, with the addition of the external gain, the frequency range of oscillation can be further extended. The proposed work is verified by computer simulation with the use of 180 nm complementary metal–oxide–semiconductor (CMOS) model parameters. The simulation gives satisfactory results of two sinusoidal output signals in quadrature with some small total harmonic distortions (THD). In addition, a circuit experiment is performed using the commercial operational transconductance amplifiers LM13700 as the active components. The circuit experiment also demonstrates satisfactory outcome which confirms the validity of the proposed circuit.